2016
DOI: 10.3390/molecules21050611
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and in Vitro Antiproliferative Evaluation of C-13 Epimers of Triazolyl-d-Secoestrone Alcohols: The First Potent 13α-d-Secoestrone Derivative

Abstract: Abstract:The syntheses of C-13 epimeric 3-[(1-benzyl-1,2,3-triazol-4-yl)methoxy]-D-secoestrones are reported. Triazoles were prepared from 3-(prop-2-inyloxy)-D-secoalcohols and p-substituted benzyl azides via Cu(I)-catalyzed azide-alkyne cycloaddition (CuAAC). The antiproliferative activities of the products and their precursors were determined in vitro against a panel of human adherent cervical (HeLa, SiHa and C33A), breast (MCF-7, MDA-MB-231, MDA-MB-361 and T47D) and ovarian (A2780) cell lines by means of MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Among these analogs, a compound with a 3-triazole substituent (D-SET) was found to the most effective on cervical carcinoma cell lines, while it has no significant inhibitory effect on the non-cancerous human fetal lung fibroblast (MRC-5) cells. We also reported that the antiproliferative effectivity and tumor selectivity of D-SET is more potent than that of cisplatin [61], a drug regularly used in cervical tumor therapy [32]. In view of these data, we performed other steroid analogs such as the natural steroid alkaloid solanidine, the natural estrogen metabolite 2-ME or the synthetic D-homoestrone [12,55,57].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Among these analogs, a compound with a 3-triazole substituent (D-SET) was found to the most effective on cervical carcinoma cell lines, while it has no significant inhibitory effect on the non-cancerous human fetal lung fibroblast (MRC-5) cells. We also reported that the antiproliferative effectivity and tumor selectivity of D-SET is more potent than that of cisplatin [61], a drug regularly used in cervical tumor therapy [32]. In view of these data, we performed other steroid analogs such as the natural steroid alkaloid solanidine, the natural estrogen metabolite 2-ME or the synthetic D-homoestrone [12,55,57].…”
Section: Discussionmentioning
confidence: 95%
“…In view of the previously mentioned most active secoalcohol, new analogs have been designed and proliferation-inhibitory effects have been detected. As expected, the derivatives with triazole substituents demonstrated the most pronounced anticancer effect on several malignant tumor cell lines tested [32].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations